Characterization of hydroxyapatite derived from eggshells for medical implants. (2019) - Das Lala, Sumit; Deb, Payel; Barua, Emon; Deoghare, Ashish.B.; Chatterjee, Sushovan
Abstract: Nano-sized Hydroxyapatite (HAp) powders are synthesized from natural bio-waste chicken eggshell. The synthesized powder is characterized using X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) which confirms the formation of HAp. Scanning Electron Microscopy (SEM) shows highly porous agglomerated HAp powder with average pore diameter of 276.3 nm. EDAX analysis reveals calcium and phosphate ratio (Ca/P) of 1.74 showing close resemblance to human bone. Transmission electron microscopy (TEM) reveals formation of spherical shaped HAp powder with average particle size of 78 nm. The synthesized nano HAp powder is suitable for coating on medical implants.